2015
DOI: 10.1079/pavsnnr201510025
|View full text |Cite
|
Sign up to set email alerts
|

Growth of local food systems: a review of potential food safety implications.

Abstract: A major challenge for livestock farming systems (LFSs) is to reconcile production with the management of natural resources, especially biodiversity and ecosystem services. Based on a review of research conducted on grassland-and rangeland-based LFSs, this paper addresses this challenge by analysing biodiversity as a product of and a key resource for LFSs. Although most studies reveal antagonisms between biodiversity and production, our findings show that it is possible to move towards synergies. The literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 160 publications
0
4
0
Order By: Relevance
“…Worsfold et al (2004) investigated farmers' market consumers' food safety concerns and reported that most (86%) consumers have few or no concerns about the safety of the food available for purchase. However, as outlined in several recent reviews (Sirsat et al, 2015;Wright et al, 2015), foodborne disease outbreaks linked to farmers' markets have been reported in the past decade, and therefore, it is necessary to increase consumers' food safety awareness towards food products available at farmers' markets in order to better protect public health.…”
Section: Discussionmentioning
confidence: 99%
“…Worsfold et al (2004) investigated farmers' market consumers' food safety concerns and reported that most (86%) consumers have few or no concerns about the safety of the food available for purchase. However, as outlined in several recent reviews (Sirsat et al, 2015;Wright et al, 2015), foodborne disease outbreaks linked to farmers' markets have been reported in the past decade, and therefore, it is necessary to increase consumers' food safety awareness towards food products available at farmers' markets in order to better protect public health.…”
Section: Discussionmentioning
confidence: 99%
“…In many countries around the world, farmers’ markets or local food markets are popular settings that facilitate consumer access to local fresh produce. Despite concerns regarding the food safety procedures in such markets [ 52 ], the potential higher prevalence of microbial contamination in the products sold in farmers’ markets compared with other retailers remains controversial [ 47 , 53 ].…”
Section: Post-harvest Management In the Fresh Produce Supply Chain And Interactions Between Safety And Sustainabilitymentioning
confidence: 99%
“…These very poor ratios affected herd sustainability, even though performance levels for replacement heifers were better ( Table 1) Hn: Holstein; Mo: Montbeliarde; AI: artificial insemination. 1 Percentage of pregnant cows served once or twice. 2 Percentage of animals calving after being served during the breeding period.…”
Section: Animal Contribution (Plasticity) To System Flexibility In Anmentioning
confidence: 99%
“…Incorporating the precepts of sustainable development in order to build and assess new technical agricultural systems hinges on breaking away from the rationales underpinning these systems and moving towards more holistic objectives encompassing far more than the simple production output function [1]. There are two key drivers to this breakaway: (i) reinventing how researchers interact with the other actors involved in the process of developing new systems and their multiple outcomes [2,3], and (ii) producing tools capable of quickly rendering a priori system assessments [4,5] as a first step towards subsequently deploying the systems in compliance with complex multicriteria specifications [6].…”
Section: Introductionmentioning
confidence: 99%